Outcomes of kidney transplantation in patients with myeloma and amyloidosis in the USA. Issue 12 (10th June 2022) - Ng, Jia H; Izard, Stephanie; Murakami, Naoka; Jhaveri, Kenar D; Sharma, Amy; Nair, Vinay
ABSTRACT: Background: Recent improvement in treatment and patient survival has opened the eligibility of kidney transplantation to patients who developed end-stage kidney disease (ESKD) from plasma cell dyscrasias (PCDs). Data on clinical outcomes in this population are lacking. Methods: We conducted a retrospective study of United Network for Organ Sharing/Organ Procurement and Transplantation Network dataset (2006–2018) to compare patient and graft outcomes of kidney transplant recipients with ESKD due to PCD versus other causes. Results: Among 168  369 adult first kidney transplant recipients, 0.22–0.43% per year had PCD as the cause of ESKD. The PCD group had worse survival than the non-PCD group for both living and deceased donor types {adjusted hazard ratio [aHR] 2.24 [95% confidence interval (CI) 1.67–2.99] and aHR 1.40 [95% CI 1.08–1.83], respectively}. The PCD group had worse survival than the diabetes group, but only among living donors [aHR 1.87 (95% CI 1.37–2.53) versus aHR 1.16 (95% CI 0.89–1.2)]. Graft survival in patients with PCD were worse than non-PCD in both living and deceased donors [aHR 1.72 (95% CI 1.91–2.56) and aHR 1.30 (95% CI 1.03–1.66)]. Patient and graft survival were worse in amyloidosis but not statistically different in multiple myeloma compared with the non-PCD group. Conclusion: The study data are crucial when determining kidney transplant eligibility and when discussing transplant risks in patients with PCD. Graphical Abstract: